Qualidade interna de ovos comerciais armazenados em refrigeradores domésticos - ARRUDA, Milena Raiane Silva de,; SILVA, Giovana Seizer,; BARONI, Thaís de Abreu Toledo,; SANTOS, Thais Laine da Rocha,; SERVIN, Zathia Rosa Soliz,; GARCIA, Elis Regina de Moraes, (ANAIS DO ENIC, 2025)
-